Surface Modifying Doped Silicon Nanowire Based Solar Cells for Applications in Biosensing. Issue 2 (29th October 2018) - Smith, Rasheid; Duan, Wenqi; Quarterman, Juliana; Morris, Angie; Collie, Ceryce; Black, Marcie; Toor, Fatima; Salem, Aliasger K.
Abstract: There is a growing demand for biosensors that are reliable, accurate, rapid, and cost effective. Appropriately functionalized silicon nanowires (SiNWs) have offered an alternative to the gold standards of enzyme linked immunosorbent assay (ELISA) and polymerase chain reaction (PCR)‐based detection of proteins and DNA, respectively, by offering rapid label‐free accurate detection of analytes. However, a major barrier limiting the progression of this technology is the cost of fabricating uniform functional nanowires (NWs) for biosensing and electrically contacting these NWs. Preliminary results are presented demonstrating the feasibility of a novel class of SiNW‐based biosensor, which alleviates these issues. The SiNW‐based biosensor presented here uses a SiNW‐based solar cell (SiNW‐SC) as a transducing element. It is demonstrated that SiNW‐SCs can be modified by anchoring monoclonal antibodies specific for prostate‐specific antigen (PSA) to the surface of SiNW‐SCs. This surface modification allows for an increase in binding of PSA to the SiNW structures, which causes an increase in short‐circuit density of SiNW‐SCs when exposed to light and PSA. This paves the way for the development of a novel class of SiNW‐based biosensors using surface modification of SiNW‐SCs. Abstract : Through functionalization, silicon nanowire based solar cells (SiNW‐SCs) can be repurposed as a biosensor for prostate specific antigen (PSA). Functionalization creates a biointerface which allows for an increase in surface binding of PSA, which in turn increases the short circuit density of the SiNW‐SCs when exposed to light.